PELAKSANAAN TERAPI REALITAS DALAM MEMBENTUK KONTROL DIRI PADA ANAK PELAKU KEKERASAN FISIK DI BALAI SENTRA ABISEKA PEKANBARU - Fatmawati; Khalisa Hanifah; Listiawati (LPPM STISIP Persada Bunda, 2023)
Adolescence is a transitional period where adolescents have doubts about the role they must perform or can be called a period of self-discovery. For this reason, many cases occur due to deviant behavior caused by adolescents, especially in acts of physical violence. The purpose of this study is to find out how the implementation of reality therapy in forming self-control in adolescents perpetrators of physical violence at the Abiseka Center Center of the Ministry of Social Affairs of the Republic of Indonesia Rumbai-Pekanbaru as a Technical Implementation Unit for social rehabilitation. The research methods used are descriptive qualitative, data collection techniques, namely observation, interviews and documentation. The results of the studies conducted show that reality therapy has been carried out in the formation of self-control in children perpetrators of physical violence. Although reality therapy has been implemented to the fullest, there are still adolescent perpetrators of physical violence whose behavior has not changed much. From this it has been seen that the implementation of reality therapy in forming self-control is not entirely successful in all adolescent perpetrators of physical violence. Â Keywords: Reality Therapy, Self-Control, Child Immorality.